Recombinant Activated Factor VII in Aortic Surgery for Patients Under Hypothermic Circulatory Arrest - Ise H; Ushioda R; Kanda H; Kimura F; Saijo Y; Akhyari P; Lichtenberg A; Kamiya H (Dove Medical Press, 2022)
Hayato Ise,1,2 Ryohei Ushioda,1 Hirotsugu Kanda,3 Fumiaki Kimura,4 Yasuaki Saijo,5 Payam Akhyari,2 Artur Lichtenberg,2 Hiroyuki Kamiya1 1Department of Cardiac Surgery, Asahikawa Medical University, Asahikawa, Japan; 2Department of Cardiovascular Surgery, Heinrich Heine University, Düsseldorf, Germany; 3Department of Anesthesiology and Critical Care Medicine, Asahikawa Medical University, Asahikawa, Japan; 4Department of Cardiovascular Surgery, Kushiro Kojinkai Memorial Hospital, Kushiro, Japan; 5Division of Public Health and Epidemiology, Department of Social Medicine, Asahikawa Medical University, Asahikawa, JapanCorrespondence: Hirotsugu Kanda, Department of Anesthesiology and Critical Care Medicine, Asahikawa Medical University, Midorigaoka-Higashi 2-1-1-1, Asahikawa, 078-8510, Japan, Tel +81-166-68-2583, Fax +81-166-68-2589, Email hirotsugukanda0629@gmail.comPurpose: We aimed to identify the risk factors of critical bleeding and investigate the safety of recombinant activated factor VII (rFVIIa) in aortic surgery under hypothermic circulatory arrest (HCA).Patients and Methods: The present single-center retrospective study compared the baseline characteristics of 144 patients who underwent aortic surgery under HCA at our institute. Among the total cohort of 144 patients, 42 received rFVIIa (rFVIIa group), while the remaining 102 patients did not (non-rFVIIa group). Perioperative bleeding and transfusions, postoperative 30-day mortality, and adverse events (AEs) were analyzed in 29 propensity score-matched pairs.Results: Before surgery, the rFVIIa group demonstrated a greater number of shocks (p=0.019), higher JapanSCORE II mortality rate (p=0.033), low platelet count (p=0.015) and fibrinogen (p< 0.001) level, prolonged activated partial thromboplastin time (aPTT) (p=0.005) and prothrombin time international normalized ratio (PT-INR) (p=0.006), and longer aortic cross clamp time (p=0.049). Postoperative bleeding, transfusion, 30-day mortality, and AEs were comparable between the groups both in the entire-unmatched cohort and propensity score matching cohort.Conclusion: Preoperative shock, higher JapanSCORE II mortality rates, low platelet and fibrinogen levels, prolonged aPTT and PT-INR, and longer aortic clamping time might be risk factors for excessive bleeding and indicate the need for rFVIIa treatment. The present study suggests that rFVIIa can be safely used to address critical and continuous bleeding in spite of adequate transfusion and supplementation of other coagulation factors in aortic surgery under HCA, without an increase in 30-day mortality and AEs.Keywords: aortic surgery under hypothermic circulatory arrest, cardiac surgery, recombinant activated factor VII, retrospective study, uncontrollable bleeding